Catalytic Enantioselective Synthesis of 4-Amino-5-aryltetrahydro-1H-benzo[c]azepines by an Aminoarylation Reaction - Akhtar, Sk Md Samim; Hajra, Saumen (Synlett, 2022)
A one-pot asymmetric aminoarylation reaction has been executed for the synthesis of trans-4-amino-5-aryltetrahydrobenzo[c]azepines with excellent diastereo- and enantioselectivity (dr > 99: 1; ee ≤97%). The reaction progresses through aziridination of prochiral N-tosyl-N-cinnamylbenzylamines, followed by an intramolecular 7-endo-tet Friedel–Crafts cyclization of the tethered aziridines generated in situ, where the combination of Cu(OTf)2 as a catalyst and PhINNs as a nitrene source was found to be effective. A chiral indenyl bis(oxazoline) was shown to be an efficient ligand for the catalytic enantioselective version of this one-pot transformation. This 7-endo-tet cyclization is contrary to the Baldwin cyclization rules.
Keywords: tetrahydrobenzazepines; asymmetric catalysis; aminoarylation; aziridines; Friedel–Crafts reaction; endo-tet cyclization